Implementation of the Sabhara Unit Two-Wheel Patrol in Preventing Crime of Motor Vehicle Theft: Implementasi Patroli Roda Dua Satuan Sabhara dalam Mencegah Tindak Pidana Curanmor - Ajeng Sekarningrat Ajeng (Indonesian Journal of Police Studies, 2021)
The number of motor vehicle thefts in the Ciamis Police area has increased every year. The purpose of this study is to describe and analyze the implementation of the two-wheeled patrol of the Sabhara Unit in preventing the occurrence of curanmor in the jurisdiction of the Ciamis Police and the factors that influence the implementation of the two-wheeled patrol of the Sabhara Unit in preventing curanmor crime in the jurisdiction of the Ciamis Police. The theories and concepts used to analyze this research are management theory, role theory, crime prevention theory, patrol concept, two-wheeled patrol concept and curanmor concept. The research method uses a qualitative approach whose results are reinforced by the presence of findings, observations, document studies, and interviews with information sources. The results showed that the two-wheeled patrols carried out by the Sabhara Unit of the Ciamis Police had been carried out but it was still not optimal because it was proven to have increased in the last 3 years. This is due to factors that hinder patrol operations. Among them are the lack of communication between the two-wheeled patrol members of the Sabhara Unit and the community which causes a lack of understanding from the community about maintaining human rights, the uneven use of two-wheeled patrols and four-wheeled patrols, the existence of supporting and inhibiting factors. Based on the results of the research, there is a need to increase understanding of the importance of maintaining dignity and social security which is socialized by two-wheeled patrol members of the Sabhara Unit to the surrounding community, there is equalization between the implementation of two-wheeled patrols and four-wheeled patrols carried out in accordance with the established rengiat, and increasing the supporting factors for patrol implementation two wheels and also minimizing the inhibiting factor in the implementation of the two-wheel patrol of the Ciamis Police Sabhara unit.